Trajetória acadêmica: experiência universitária no curso de Pedagogia - Silva, Maria Alceniza Viana da (Brasil, 2024)
This Final Course Work presents an academic memorial detailing my trajectory throughout my degree, with an emphasis on the experiences and learning acquired during this period. The main objective is to reflect on the gradual and professional development obtained through the university experience, highlighting the main challenges faced, the achievements achieved and the significant influences that shaped my training. In the course of the work, the most important phases of my academic journey are addressed, from entering university to completing the course. Reports are presented on extracurricular activities, research projects, internships and participation in academic events, as well as integration and collaboration experiences with colleagues and teachers. The memorial also seeks to highlight the impact of higher education on my knowledge, skills and competencies, as well as on the formation of ethical and social values. Through this reflection, I seek to contribute to a broader understanding of the role of the university in the integral development of students. Keywords: Academic Report; University Experience; Personal Development; Education.